Optimum performance in the badminton jump smash - Miller, R.; Felton, P. J.; McErlain-Naylor, S. A.; Towler, H.; King, M. A. (World Badminton Federation, 2016)
The badminton smash is an essential component of a player`s repertoire and a significant stroke in gaining success as it is the most common winning shot, accounting for 53.9% of winning shots (Tsai and Chang, 1998; Tong and Hong, 2000; Rambely et al., 2005). The speed of the shuttlecock exceeds that of any other racket sport projectile with a maximum shuttle speed of 493 km/h (306 mph) reported in 2013 by Tan Boon Heong. If a player is able to cause the shuttle to travel at a higher velocity and give the opponent less reaction time to the shot, it would be expected that the smash would be a more effective weapon (Kollath, 1996; Sakurai and Ohtsuki, 2000). There is limited research exploring the biomechanics involved in the badminton smash. However research into other sports, involving motions very similar to the badminton smash (tennis serve, overarm throw), are also able to help give insight into the mechanisms involved in the badminton smash. Waddell and Gowitzke (2000); Lees (2002) and Lees et al. (2008) demonstrate that several biomechanical principles can be applied to the badminton smash, and suggest how these can improve performance and shuttle velocity. These are increasing the range of motion of joint actions to allow a greater acceleration and more use of muscular force, the use of proximal-to-distal sequencing and the stretch-shortening cycle.